A bibliometric analysis of telerehabilitation services for patients with stroke - Wu, Dan; Zhang, Haojie; Leng, Yan; Li, Kai; Li, Shijue; Lo, Wai Leung Ambrose (Frontiers in Neurology, 2023)
Background: Routine rehabilitation service was disrupted during the COVID-19 pandemic outbreak. Telehealth was identified as an alternative mean to provide access to service. This bibliometric study aimed to analysis the scientific literature to discover trends and topics in the application of telerehabilitation in patients with stroke. Methods: The Web of Science electronic database was searched to retrieve relevant publications on telerehabilitation. Bibliometric data，including visual knowledge maps of authors, countries, institutions and references were analyzed in CiteSpace. Visualization maps were generated in VOSviewer to illustrate the recurring keywords and countries that are productive in this research area. Results: The analysis was based of 6787 publications. The number of publications peaked between the year of 2019 and 2021, which coincided with the years for the outbreak of COVID-19. A total of 113 countries from Europe, North America, Asia and Oceania had at least one publication in this research field, implying the worldwide attention in this research area. Nine out of the 10 most productive countries are developed countries, indicating the potential higher capability to implement telerehabilitation program. Conclusion: The potential benefits and diversity of telerehabilitation are already highly visible from clinical studies, and further improvement in these technologies are expected to enhance functionality and accessibility to patients. More relevant research is encouraged to understand the barriers to increase adaption of telerehabilitation service, which will finally translate to significant therapeutic or preventative impact.